AFC Energy hitting milestones to commercialise large-scale alkaline fuel cell systems. (December 2015) - Barrett, Steve
Abstract : UK-based AFC Energy is developing alkaline fuel cell technology, and will shortly have a demonstration system operational in Stade, Germany as part of the EU-funded Power-Up project. We caught up with CEO Adam Bond, to find out how the company is approaching commercialisation, and talked about the challenge of its well-publicised milestones.